Interstitial pulmonary fibrosis in a Malaysian captive Asian elephant (Elephas maximus) - Yakubu, Yusuf; Ong, Bee Lee; Mohamed Mustapha, Noordin; Zakaria, Zunita; Jayaseelan, K.; Kumar Sharma, Reuben Sunil; Sugnaseelan, Sumita; Firdaus, M.; Kamarudin, Zubaidah; Ngeow, Yun Fong (Veterinary Association Malaysia, 2014)
A 14-year-old female captive Asian elephant in a Malaysian z oo with a history of positive sero-reactivity to Elephant TB STAT-PAK assay was humanely euthanized due to chronic weight loss and poor response to treatment. Postmortem revealed generalized congestion and emphysematous lungs. Microscopically, there were severe pulmonary emphysema, eosinophilic hyaline membrane and infiltration of mature fibrocytes in the alveolar walls. Based on the histopathological findings interstitial pulmonary fibrosis was diagnosed. The possible cause of which although not completely known, is most likely due to hypersensitivity. The allergic reaction could have been caused by exposure to antigens of avian origin or the Mycobacterium gilvum, an non-tuberculous mycobacterium (NTM), isolated from the lung. This is the second case reported in elephants globally, thought it has been well studied in humans and reported in horses. Providing good husbandry for elephants in captivity is important to reduce the occurrence of such condition.